Automatic analysis of microscopic photo-pictures of undeveloped and developed nuclear emulsions. (December 2015) - Ditlov, V.; Berezkina, U.; Kuznetsov, A.; Orurk, O.; Senchinkov, E.
Abstract: Methods of automatic computer analyses of images have large impotence in numerous physical problems with different kinds of radiations, which use such solid-state detectors as nuclear photographic emulsions, plastics and others. We described a method of expanding boundaries of dark areas for such computer analyses of micro-pictures. We demonstrated effectiveness of this method by the example of the search of microcrystals size distributions in two undeveloped nuclear emulsions and similar distribution of background grains in the developed emulsion. Highlights: This work deals with automatic analysis of micro-images in nuclear photoemulsions. A simple method of expanding regions for micro-image analyses was described. Its efficiency was tested for measurement of distributions of AgBr microcrystal sizes. Either its efficiency was tested for measurement of distributions of developed grains. This method is designed for numerous physical problems of nuclei and particles.